The Free Boundary Problem in Biological Phenomena (Journal of Partial Differential Equations, 2007)
We prove the local existence of weak solution of a free boundary problem for a hyperbolic-parabolic system.
Keywords: Hyperbolic-parabolic system; free boundary; external signal